Relasionalitas “Aku” dan “Engkau” dalam Masyarakat Indonesia yang Majemuk Sebagai Gambaran dari Relasionalitas Trinitas - Gregorius Pasi (Studia Philosophica et Theologica, 2020)
To the Catholic faithful, the “I” and “You” relationality of Indonesia’s pluralistic society “formulated” in the third principle of Pancasila (Persatuan Indonesia = a unified Indonesia) and in the nation’s motto “Bhineka Tunggal Ika” (Unity in Diversity) can point towards trinitary relationality. Using the critical reading approach to Pancasila and moto Bhineka Tunggal Ika, this study has discovered the four following issues: Firstly, the relationality between “I” and “You” in Indonesian society can point towards the intersubjective relationality of the Trinity. Secondly, the principle of Bhineka Tunggal Ika can point towards the principle of unity in the diversity of the Trinity. Thirdly, the transcendence of “Kami” (We-excluding-You) towards “Kita” (We-including-You) in Indonesian society can point towards the openness of the Trinity to establish unity with humans who are fundamentaly different from God. Fourthly, mutual participation relationality in Indonesian society can point towards the principle of perichoresis of the Trinity.